Colorimetric detection of specific DNA segments amplified by polymerase chain reactions. - Kemp, D J (1989)
The polymerase chain reaction (PCR) procedure has many potential applications in mass screening. We describe here a general assay for colorimetric detection of amplified DNA. The target DNA is first amplified by PCR, and then a second set of oligonucleotides, nested between the first two, is incorporated by three or more PCR cycles. These oligonucleotides bear ligands: for example, one can be biotinylated and the other can contain a site for a double-stranded DNA-binding protein. After linkage to an immobilized affinity reagent (such as a cloned DNA-binding protein, which we describe here) and labeling with a second affinity reagent (for example, avidin) linked to horseradish peroxidase, reaction with a chromogenic substrate allows detection of the amplified DNA. This amplified DNA assay (ADA) is rapid, is readily applicable to mass screening, and uses routine equipment. We show here that it can be used to detect human immunodeficiency virus sequences specifically against a background of human DNA.